Students and money management behavior of a Malaysian public university - Zulfaris, Mohd Danial; Mustafa, Hasri; Mahussin, Norlida; Alam, Md. Kausar; Mat Daud, Zaidi (Korea Distribution Science Association, 2020)
This study aims to investigate whether financial literacy, parental socialization, peer influence and self-control have a significant impact on money management among students of a Malaysian public university. In most settings, the studies on the determinants of personal saving behavior among university students focus on personality factors, attitudes toward money and possessions, and financial knowledge as predictors of money management behavior. Primary data are collected using a self-administered questionnaire with the samples comprised 186 students. The findings show that all the financial literacy and parent socialization have a positive relationship with money management; meanwhile, peer influences and self-control have a negative relationship with money management. This is because the majority of students admit they cannot control their self in managing their money. In this study, parent socialization has a significant relationship with money management which signifies that parents are playing essential roles in ensuring their children to establish money management. In practical, this study can contribute to the parents in providing their children to foster sound money management. Besides, Perbadanan Tabung Pendidikan Tinggi Nasional (National Higher Education Fund Corporation) PTPTN should monitor the loan, and management process and arrange motivational program so that students can more focus on the educational expense.